Analysis Influence Power Pull Tour Culinary Streetfood in Bandung City - Yudi Nugraha; Shierla Setyani (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
The city of Bandung is developing into a business center that has advantages in several fields, especially in the field of culinary tourism, which is part of the local identity and is growing rapidly. The purpose of this research is to see the potential of street food in Lengkong to increase the interest of culinary tourism in the city of Bandung. This research method is quantitative and phenomenological through field studies and using the internet as one of the means we use to get information about street food places in Lengkong as our analysis material. This study found that Lengkong street food culinary products can improve the economy of Bandung city traders quickly, because many food vloggers review various types of food in Lengkong so that many domestic and foreign tourists are curious about one of the street foods in the city of Bandung. Social media also plays an important role as a development or form of promotion to increase more tourists and advance local SMEs within the scope of the Lengkong area and develop interest in culinary tourism in the city of Bandung.